Association of the Monocyte to HDL-cholesterol Ratio with Idiopathic Pulmonary Arterial Hypertension and Disease Severity - Solmaz, Hatice; Akbulut, Mehmet (My University, 2022)
Objective: Idiopathic pulmonary arterial hypertension (IPAH) is a disease characterized by abnormal vascular changes in the pulmonary arteries, leading to elevated pulmonary artery pressure. In this retrospective study, we investigated the role of monocyte to high-density lipoprotein-cholesterol ratio in predicting IPAH and disease severity. Methods: Thirty-three patients with IPAH were compared with the 25 healthy controls according to their demographic characteristics, laboratory and echocardiographic parameters. Baseline and year 1 data of patients with pulmonary hypertension who received drug-therapy were also compared. The predictive value of the monocyte to high-density lipoprotein-cholesterol ratio for IPAH and its change with disease severity were examined. Results: The monocyte to high-density lipoprotein-cholesterol ratio was significantly higher in patients with IPAH (p=0.009). In receiver operating characteristic curve analysis, monocyte to high-density lipoprotein-cholesterol ratio >11.05% predicted idiopathic pulmonary hypertension. In drug-treated patients, monocyte to high-density lipoprotein-cholesterol ratio in year 1 was significantly lower than the baseline (p<0.001). Among the patients with pulmonary hypertension, the group in which risk stratification improved from high risk to low showed the greatest reduction in monocyte to high-density lipoprotein-cholesterol ratio. A significant positive correlation was found between the percentage reduction in monocyte to high-density lipoprotein-cholesterol ratio and the percentage reduction in pulmonary vascular resistance from baseline to year 1 (p=0.003). Conclusion: Monocyte to high-density lipoprotein-cholesterol ratio may be a promising parameter in the assessment and management of patients with IPAH.
Keywords: Solunum Sistemi; Genel ve Dahili Tıp